Spis prac licencjackich, magisterskich i doktorskich z zakresu nauki o książce, informacji naukowej i czasopiśmiennictwa powstałych w katedrze bibliotekoznawstwa UŁ w latach 2006-2010 - Walczak-Niewiadomska, Agata (Acta Universitatis Lodziensis. Folia Librorum, 2010)
Mentioned above list contains Bachelor, MA and doctor dissertations titles concerning library science and periodical press made at the University of Łódź in the years 2006-2010. It is the continuation of formerly published lists from the years 1950-2005. Authors surnames are in alphabetical order with professor’s surname and the year of graduation next to it. The list is completed with professors, chronological and subject indices. All the thesis from the list are in Department’s Library and University files.